Childbearing under different family policy schemes - Ezdi, Sehar; Kilpi-Jakonen, Elina; Pöyliö, Heta; Erola, Jani (University of Bamberg Press, 2025)
Objective:
This study assesses whether and how changes in family policies are associated with first and second births in Finland, Germany and the United Kingdom, and whether these associations differ by women's education.
Background:
Family policies are expected to impact the direct and indirect costs of childbearing by providing resources that influence the monetary and non-monetary costs of having children. The countries analysed here have undergone substantial changes in family policy throughout the two decades analysed, but each country has changed different aspects of their policies, and they have done so in different policy environments.
Method:
We analysed women aged 18-44 and their transitions to first and second births using register data from Finland (N = 57,518 / 21,685) and panel data from Germany (G-SOEP, N=37,716 / 16,756) and the UK (BHPS and Understanding Society, N = 13,213 / 9,992) complemented with annual family policy information. The data were analysed using logistic regression models and interactions, and the results are presented as average marginal effects.
Results:
The results suggest that the association between changes in family policies and transitions to first and second child birth varied by birth parity, women's education level, and between countries. For example in Finland, increases in paternity leave length were associated with greater propensities to transition to first birth for highly educated women, whereas increases in child allowances had a similar association for lower educated women. In Germany, reductions in maternity leave length were associated with increased transitions to first birth for higher educated women. In the UK, increases in maternity leave length were associated with greater transitions to first births among all women.
Conclusion:
The results highlight that to the extent that family policies influence fertility, they do so depending on both the country context and often differentially within countries based on women's education level and birth parity.